One Thousand Three Hundred Years of Variability in the Position of the South Pacific Convergence Zone. Issue 17 (25th August 2020) - Higgins, P. A.; Palmer, J. G.; Turney, C. S. M.; Andersen, M. S.; Cook, E. R.
Abstract: The South Pacific Convergence Zone (SPCZ) is the largest rain belt in the Southern Hemisphere and a key driver of precipitation variability, impacting South Pacific island communities. Our millennial‐long reconstruction is based on a trans‐Pacific tree‐ring network, containing chronologies sensitive to changes in the SPCZ because of its pervasive nature, spatial extent, and link to the El Niño‐Southern Oscillation. The reconstruction explains 58% of variance in the instrumental SPCZ index from 1911–1998. El Niño‐Southern Oscillation cycles are identified throughout the reconstruction period. Multidecadal periodicities wax and wane, coinciding with a sustained eastward shift during the Medieval Climate Anomaly ( 1, 000–1, 200 CE). We find large volcanic eruptions increased the tendency for the SPCZ to be displaced eastward. The reconstruction helps improve our understanding of past hydroclimatic behavior in the southwest Pacific and can be used to validate general circulation model projections for Pacific Island communities and the wider region in the 21st century. Plain Language Summary: South Pacific island communities experience significant variability in their rainfall between seasons, across years, and between decades. This variability is due to changes in the average position and intensity of the South Pacific Convergence Zone (SPCZ), the largest rain belt in the Southern Hemisphere. The SPCZ tends to move from east to west in response to changes in sea surface temperatures and winds that accompany the El Niño‐Southern Oscillation. Lower frequency variability is also present in the SPCZ; however, this variability is poorly understood because data records from the region are too short. In this research, we extended the record of SPCZ variability back in time to 700 CE using a statistical model based on moisture‐sensitive tree‐ring records from both sides of the Pacific. We analyzed the SPCZ reconstruction during periods when the average climate conditions were different from today and assessed the impact that changes in solar output and volcanic eruptions may have had during these periods. This research helps us to understand the long‐term behavior of the SPCZ, which is essential to understand how it may change under future climate conditions. Key Points: A 1, 300‐year reconstruction of the South Pacific Convergence Zone Index using a trans‐Pacific network of tree‐ring chronologies The reconstruction identifies pervasive El Niño‐Southern Oscillation periodicities throughout the reconstruction period The reconstruction also identifies the Medieval Climate Anomaly ( 1, 000–1, 200 CE) and the influence of large tropical volcanic eruptions